Incidence of congestive heart failure in rheumatoid arthritis: a review of literature and meta‐regression analysis. (7th October 2020) - Khalid, Yaser; Dasu, Neethi; Shah, Ankit; Brown, Keith; Kaell, Alan; Levine, Adam; Dasu, Kirti; Raminfard, Albert
Abstract: Aims: Rheumatoid arthritis (RA) is a systemic inflammatory autoimmune disorder that not only affects peripheral joints but also increases the risk for cardiovascular disease (CVD) and mortality. Heart failure (HF) appears to be one of the most important contributors to the excess mortality risk among patients with RA. We assessed the incidence of HF in patients with RA compared with age‐matched and sex‐matched non‐RA subjects, after accounting for traditional cardiovascular risk factors and clinical ischemic heart disease. Methods and results: We performed an aggregate analysis on three studies of RA patients having listed manifestations of HF. We performed a meta‐regression analysis to evaluate the incidence of HF in RA patients with increased age and noted for any gender correlation. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using both fixed‐effects and random‐effects models. In the cumulative analysis of 5, 220, 883 patients, the incidence of HF was noted to be almost two‐fold higher in patients with RA compared with a matched control population (OR 1.78, 95% CI 1.22–2.60, P < 0.003), HTN (OR 1.66, 95% CI 1.24–2.23, P < 0.001), and diabetes (OR 1.57, 95% CI 1.36–1.81, P < 0.001). Women had three‐fold higher incidence of HF with RA (OR 3.38, 95% CI 2.59–4.40, P < 0.001). On meta‐regression, the incidence of HF increased further with older age (coefficient = 0.12, P = 0.0004). Conclusions: Our systematic review that included over 5 million subjects confirms the suspected increased incidence of HF in RA patients. Women have the greatest risk for HF. Our analysis advocates the need for updating the current guidelines to incorporate screening and preventive methods for HF in RA patients.